1978
DOI: 10.1111/j.1432-1033.1978.tb12225.x
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐State Kinetic Studies on Adenylate Cyclase from Brevibacterium liquefaciens

Abstract: Kinetic data of basal adenylate cyclase activity were found to be in agreement with a negatively cooperative model for this enzyme. The model assumes a dimeric structure for the enzyme with two binding sites per dimer. The binding of the first substrate molecule increases the dissociation constant for substrate molecules increases the dissociation constant for substrate molecules at the second site. However, the doubly occupied enzyme has a greater catalytic efficiency per site than the singly occupied species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although these authors found that pyruvate was required for activity of the crystalline enzyme, they left the mode of interaction between the enzyme and its substrate open to question (49). In a study of the steady-state kinetics of the adenyl cyclase of B. Ziquefaciens Ozer and Scheit suggested that activation by pyruvate involves abolishing "negative cooperativity" between the subunits of the cyclase, with concomitant induction of a better fit of the enzyme for its substrate (38 …”
Section: We Found That Itmentioning
confidence: 99%
“…Although these authors found that pyruvate was required for activity of the crystalline enzyme, they left the mode of interaction between the enzyme and its substrate open to question (49). In a study of the steady-state kinetics of the adenyl cyclase of B. Ziquefaciens Ozer and Scheit suggested that activation by pyruvate involves abolishing "negative cooperativity" between the subunits of the cyclase, with concomitant induction of a better fit of the enzyme for its substrate (38 …”
Section: We Found That Itmentioning
confidence: 99%